Donor Cell Myeloid Sarcoma. (14th April 2014) - Walshauser, Mark A.; Go, Aileen; Sojitra, Payal; Venkataraman, Girish; Stiff, Patrick
Abstract : Donor cell derived malignancies are a rare and interesting complication of allogeneic bone marrow transplantation. We present a case of a 56-year-old male with donor cell myeloid sarcoma of the stomach and myocardium.